Implementation fidelity in a multifaceted program to foster rational antibiotics use in primary care: an observational study - Kühn, Lukas; Kronsteiner, Dorothea; Kaufmann-Kolle, Petra; Andres, Edith; Szecsenyi, Joachim; Wensing, Michel; Poß-Doering, Regina (BMC medical research methodology, 2022)
The ARena study (Sustainable Reduction of Antimicrobial Resistance in German Ambulatory Care) is a three-arm, cluster randomized trial to evaluate a multifaceted implementation program in a German primary care setting. In the context of a prospective process evaluation conducted alongside ARena, this study aimed to document and explore fidelity of the implementation program.